Novel rotational motion actuated beam-type multistable metastructures. (December 2022) - Pan, Diankun; Xu, Yulong; Li, Wenbing; Wu, Zhangming
Graphical abstract: Highlights: A family of rotational motion actuated multistable metastructures is proposed based on pre-shaped bistable beams. An analytical model is established to obtain the design criteria for the bistable beam unit. The basic bistable structure with one layer is designed, which can achieve a rotation angle of 1 rad. Multistable structures with more layers that can achieve the large rotation with desired snapping sequence are explored. Abstract: This work aims to explore and design a family of multistable metastructures, which are actuated by rotational motion. The bi-stability design criteria for a single pre-shaped beam unit are studied firstly using an analytical model and finite element method. Based on this bi-stability study, a typical one-layer of this novel rotational motion actuated bistable structure, which is composed of four pre-shaped beams assembled uniformly inside two circular frames, is proposed and fabricated. The mechanical behaviour of this bistable structure represented in terms of moment-angle curves are analyzed by the finite element method and experiments. A parametric analysis is performed to study the influence of geometric parameters of an one-layer multistable metastructure on its bi-stability performance, which provides the guidance to design multistable structures with more layers. Lastly, multistable structures with two layers and three layers, which can achieve large rotations with controllable angle-step and snapping sequence, are designed and studied. Furthermore, this research demonstrates other as-fabricated beams with bi-stability have prospects to design the rotational multistable metastructures. The multistable metastructures proposed in this work create new opportunities to design advanced reconfigurable structures and devices.